KORELASI NILAI UKG DENGAN KETERAMPILAN PEDAGOGIK GURU GEOGRAFI SMA KABUPATEN AGAM - Nuri Hidayati; Syafri Anwar (DEPARTEMEN GEOGRAFI FIS UNP, 2021)
This research was conducted to see how the level of teacher pedagogical skills and the relationship between UKG scores and the pedagogical skills of geography teacher at senior high schools in Agam District. This type of research is quantitative using correlational techniques. The research was conducted in Agam District, and was conducted from April to May 2020. The study population was geography teachers at senior high schools in Agam District. The research sample was a geography teacher at senior high schools in Agam District who had a UKG score. Data collection techniques were obtained through questionnaires and documentation. The data analysis technique is obtained through validity, normality test and hypothesis testing. The results showed that: (1) the pedagogical skill level of the geography teacher at senior high schools in Agam was in the good category, namely 35.3%; (2) has a positive and significant correlation between the UKG score and pedagogic skills with a correlation coefficient of 0.67, this means that the relationships between the two is highly correlated.